Respuesta :
-18 - 6k = 6 (1 + 3k)
First you want to distribute the 6 into the values within the brackets so basically multiply the two terms by 6.
-18 - 6k = 6 + 18k
next let's add 6k to both sides
-18 = 6 + 24k
now let's minus 6 from both sides
-24 = 24k
now divide 24 from both sides
-1 = k
First you want to distribute the 6 into the values within the brackets so basically multiply the two terms by 6.
-18 - 6k = 6 + 18k
next let's add 6k to both sides
-18 = 6 + 24k
now let's minus 6 from both sides
-24 = 24k
now divide 24 from both sides
-1 = k
-18-6k=6(1+3k)
-18-6k=6+18k
Putting like terms together;
18k+6k=-18-6
24k=-24
k=-1
-18-6k=6+18k
Putting like terms together;
18k+6k=-18-6
24k=-24
k=-1